Development and evaluation of bilayer tablets of combination of antibiotics for the treatment of sexually transmitted disease - Swati Sanjay Gaikwad; Sandip Annaji Chafle; Princy Sunil Morris; Jasmine Gev Avari
ABSTRACT The present research work was envisaged to develop bilayer tablets to improve therapeutic efficacy of antibiotic combination for the treatment of sexually transmitted diseases. The combination of two antibiotics i.e. cefixime trihydrate and ofloxacin were used for the preparation of bilayer tablets which act against genito-urinary infections. The formulations comprise of cefixime trihydrate as immediate release layer formulated using different superdisintegrants and ofloxacin as extended release layer containing HPMC K100M. Evaluation of bilayer tablets were performed for the immediate release cefixime layer and sustain release ofloxacin layer with optimization of excipients. The immediate release layer of cefixime showed complete release within 30 min and ofloxacin release was extended up to 24 hours. The similarity factor value of ofloxacin sustained release layer was found to be 87.01 for initial and 80.35 after 3 months stability when compared with marketed reference product. The present study revealed that cefixime trihydrate and ofloxacin bilayer tablets were successfully developed for the use against sexually transmitted infections.